PENGARUH PEMBERIAN MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA KARYAWAN HOTEL DI KOTA PEKANBARU (Studi Pada Mona Plaza Hotel Dan Stefani City Hotel Pekanbaru) - Juwita, Zelfira; Suryalena, Suryalena (Jurnal Daya Saing, 2024)
Abstract: The purpose of this research is to determine the effect of providing work motivation and the work environment on employee job satisfaction among hotel employees in the city of Pekanbaru (Study at the Mona Plaza Hotel and Stefani City Hotel Pekanbaru). This research is located on Jalan HR. Soebrantas No.18 Tuah Karya, Tampan District, Pekanbaru City. Then the location of the second research object was carried out at the Stefani City Hotel which is located on Jalan Taskurun no. 100 Wonorejo, Marpoyan Damai District, Pekanbaru City. The population in this study was 39 employees. Data analysis was carried out using statistical analysis with the help of SPSS. The sampling technique used is the census method or saturated sampling technique and data collection techniques in this research include validity test, reliability test, classical assumption test, determination test, simple linear regression analysis, multiple linear regression analysis, t test and f test and prove hypothesis. The research results show that providing work motivation and the work environment have a significant influence on employee job satisfaction. Based on results research obtained an R Square value of 0.563, meaning that 56.3% of the variables providing work motivation and work environment influence employee job satisfaction for hotel employees in the city of Pekanbaru (Study at Mona Plaza Hotel and Stefani City Hotel Pekanbaru). Keywords: Work Motivation, Work Environment, Employee Job Satisfaction